The Lipidic and Volatile Components of Coffee Pods and Capsules Packaged in an Alternative Multilayer Film - Giulia Basile; Lucia De Luca; Martina Calabrese; Gianfranco Lambiase; Fabiana Pizzolongo; Raffaele Romano (Foods, 2024)
Coffee pods and capsules require packaging that guarantees the optimal coffee preservation. The chemical composition of coffee can undergo quality decay phenomena during storage, especially in terms of lipidic and volatile components. Amongst coffee packaging, aluminum multilayer materials are particularly widely diffused. However, aluminum is a negative component because it is not recoverable in a mixed plastic structure and its specific weight gives significant weight to packaging. In this study, a multilayer film with a reduced content of aluminum was used to package coffe pods and capsules and compared to a standard film with an aluminum layer. Their influence on the peroxides and volatile organic compounds of two coffee blends, 100% Coffea arabica L., 50% Coffea arabica L., and 50% Coffea canephora var. robusta L., were studied during their 180-day shelf life. The predominant volatile organic compounds detected belonged to the class of furans and pyrazines. Both packaging materials used for both coffee blends in the pods and capsules showed no significant differences during storage. Thus, the alternative packaging with less aluminum had the same performance as the standard with the advantage of being more sustainable, reducing the packaging weight, with benefits for transportation, and preserving the coffee aroma during the shelf life.